Lipid Profile in Subfertile Clients with Premature Ovarian Failure: University of Ilorin Teaching Hospital Experience - I.M AbdulAzeez; S.A Biliaminu; A.B Okesina; A.W.O Olatinwo; L.O Omokanye (Journal of Krishna Institute of Medical Sciences University, 2018)
Background: Premature Ovarian Failure (POF) is associated with a higher incidence of cardiovascular events later in life. Concurrent with the ages of menopausal transition, a shift in lipid profile takes place. The increased burden may be mediated by a worsening of cardiovascular risk factors, such as lipids, corresponding with the loss of ovarian function. Aim and Objectives: To investigate serum lipid and hormonal levels in women with premature ovarian failure and compare with those of apparently healthy women of similar age. Material and Methods: The study was a cross-sectional one in which serum fasting Total Cholesterol (TC), Triglycerides (TG), High Density Lipoprotein Cholesterol (HDL-C) and Low Density Lipoprotein Cholesterol (LDL-C) levels were measured in 50 women with POF and compared with 40 age matched control. Serum hormonal profiles were compared with lipid profiles and biomarkers of atherogenic index were assessed. Results:Women with POF present with statistically significant elevations in the mean values of serum FSH and LH, when compared with those of controls (p<0.001), while there were significant decrease in mean levels of serum prolactin, progesterone, testosterone and oestradiol when subjects were compared with controls (p<0.001). There were statistically significant elevations in serum total cholesterol, triglycerides, HDL-C and LDL-C, in premature ovarian failure subjects when compared with controls (p<0.001). There was statistically significantly difference when mean values of artherogenic index and Castelli ratio II of subjects were compared with those of controls. Conclusion: Loss of ovarian function at a very young age (POF) was characterized with subtle changes in the serum lipid profile (higher TC, TG, HDL-C, and LDL-C levels). It also shows that atherogenic index and Castelli ratio II are better tools for assessment of atherogenicity than CHD risk ratio and Castelli ratio I in patients with POF.